Lipid Fraction from Agaricus brasiliensis as a Potential Therapeutic Agent for Lethal Sepsis in Mice - Kely Campos Navegantes Lima; Silvia Leticia de França Gaspar; Ana Ligia de Brito Oliveira; Sávio Monteiro dos Santos; Lucas Benedito Gonçalves Quadros; Juliana Pinheiro de Oliveira; Rayane Caroline dos Santos Pereira; Alexandre Guilherme da Silva Dias; Lucas da Silva Gato; Leonardo Yuji Nihira Alencar; Alanna Lorena Pimentel dos Santos; Gilson Pires Dorneles; et al. (MDPI AG, 2024)
Sepsis is a potentially fatal clinical condition that results from an immune imbalance in the host during an infection. It presents systemic alterations due to excessive activation of pro-inflammatory mediators that contribute to inflammation, formation of reactive species, and tissue damage. Anti-inflammatory mediators are then extensively activated to regulate this process, leading to immune exhaustion and, consequently, immunosuppression of the host. Considering the biological activities of the nutraceutical Agaricus brasiliensis (A. brasiliensis), such as immunomodulatory, antioxidant, and antitumor activities, the present study investigated the therapeutic potential of the lipid fraction of A. brasiliensis (LF) in a model of lethal sepsis in mice (Mus musculus), induced by cecal ligation and perforation (CLP). The results showed that treatment of septic animals with LF or LF associated with ertapenem (LF-Erta) reduced systemic inflammation, promoting improvement in clinical parameters and increased survival. The data show a reduction in pro-inflammatory and oxidative stress markers, regulation of the anti-inflammatory response and oxidizing agents, and increased bacterial clearance in the peritoneal cavity and liver. Thus, it can be concluded that LF as a treatment, and in conjunction with antibiotic therapy, has shown promising effects as a hepatoprotective, antioxidant, antimicrobial, and immunomodulatory agent.